ANALISIS SEMIOTIKA PESAN MORAL DALAM FILM JOKOWI - Ishmatun Nisa; Jumroni; Tantan Hermansah (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2022)
The Jokowi film is a fictional film based on Jokowi's childhood life, a poor child who wants to change his life until he becomes the mayor of Solo, then governor of DKI Jakarta, and now is the president of the Republic of Indonesia. Where the story of his childhood life contains many moral messages which are intended for all levels of society, especially young people. The purpose of this research is to know and understand the representations, objects, and interpretants contained in Jokowi's film. The theory used is the theory of Charles Sanders Pierce. The methodology used in this research is semiotic analysis. This research produces a moral message from the signs contained in Jokowi's film. The five scenes contain moral messages that can be emulated for children so that they instill noble qualities or morals in them. As well as being able to become a better person to achieve a glorious future. The resulting moral messages are: preserving Indonesian culture, remembering God, helping each other, religious identity, tolerance and harmony between religious communities, do not take and accept bribes, be diligent and tenacious in achieving success, and be grateful for life